2002
DOI: 10.1076/edre.8.1.129.6919
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Differentiate Mathematics Students in Cyprus, Hong Kong, and the USA

Abstract: The purpose of this study was twofold: to examine how attitudinal and instructional variables differentiated 4th-grade students in Cyprus, Hong Kong, and the USA; and to determine how those variables were related to math performance on the TIMSS test. A discriminant analysis was performed to examine how those variables differentiated the students in the 3 countries. The most striking result was that the students from all 3 countries, who were similar to the average students in Cyprus, had the highest achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 9 publications
1
20
0
4
Order By: Relevance
“…2012;Luu and Freeman 2011;Kubiatko and Vlckova 2010;Spiezia 2010;Demir and Kilic 2009) and highlighted that it was critical to develop students' skills in using computers and advanced communication technology in order to improve their learning outcomes (Lee 2009). Other researchers (Paton 2010;Sullivan 2005;Papanastasiou 2002;Fuchs and Woessman 2004;Wittwer and Senkbeil 2007;Aypay 2010), however, found negative correlations between computer use and students' achievement. For example, Wittwer and Senkbeil (2008) found that computers had no substantial influence on math performance.…”
Section: The Relationship Between Ict Use and Student Achievementmentioning
confidence: 99%
“…2012;Luu and Freeman 2011;Kubiatko and Vlckova 2010;Spiezia 2010;Demir and Kilic 2009) and highlighted that it was critical to develop students' skills in using computers and advanced communication technology in order to improve their learning outcomes (Lee 2009). Other researchers (Paton 2010;Sullivan 2005;Papanastasiou 2002;Fuchs and Woessman 2004;Wittwer and Senkbeil 2007;Aypay 2010), however, found negative correlations between computer use and students' achievement. For example, Wittwer and Senkbeil (2008) found that computers had no substantial influence on math performance.…”
Section: The Relationship Between Ict Use and Student Achievementmentioning
confidence: 99%
“…For example, the same paradox has been identified in student comparisons at the 4th (Leung, 2002;Papanastasiou, 2002), 7th, 8th (House, 2003;Shen, 2002;Wang, 2001;Wilkins, 2004), and 12th (Schreiber, 2002) grade levels in Hong Kong and the USA.…”
Section: Challenging Existing Self-concept Theories Emerging From Intmentioning
confidence: 74%
“…This interpretation is seriously challenged by the findings of several large scale, cross-national comparisons (Leung, 2002;Papanastasiou, 2002;Programme for International Student Assessment, 2004a;Schreiber, 2002;Wilkins, 2004), which showed that many of the high performing countries in mathematics correspondingly reported lower student self-concepts in mathematics learning. In contrast, students in countries with lower mathematics performance often showed higher self-concepts in mathematics at different grade levels.…”
Section: Introductionmentioning
confidence: 85%
“…Based on this knowledge, a positive change in a teacher's attitude can be said to influence attitude towards mathematics of a group he/she teaches to. Previous investigations reveal that a teacher's method of teaching is effective on the students' interest in and attitudes towards the lesson (Akyüz, 2006;Barıs, 2009;Cribari, 2006;Hare, 1999;Metin, 2001;Papanastasiou, 2002). In light of this research, it is recommended that the content of the preschool teaching undergraduate programme in Turkey be revised in terms of mathematics, an opportunity to practice be provided to preservice teachers in addition to delivering theoretical knowledge of the course on mathematics education, studies be conducted to integrate mathematics by other courses and activities, similar studies be also undertaken for inservice teachers, and their attitudes towards mathematics education be investigated and requirements of teachers who display negative attitudes be determined, common requirements be analysed and generalised by carrying out similar investigations on preservice preschool teachers in all universities.…”
Section: Resultsmentioning
confidence: 98%